ANTESEDEN DAN KONSEKUENSI KOMITMEN SUMBER DAYA MANUSIA - Widodo Widodo (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2010)
Existing human resources in the organization have diversity in the intensity of commitment,based on the condition of this article examine how to develop models of human resourcecommitment in order to improve the performance of human resources. Based on the literaturereview there are seven proposed hypotheses, supported by empirical. The better the communicationquality, the higher the performance of human resources. The better the communicationquality, the higher the commitment affective. The better the communication quality,the higher the commitment continuance. The better the communication quality, the higher thecommitment normative. The higher the affective commitment, the higher the performanceof human resources. More and continuance commitment, the higher the performance of humanresources. The more normative commitment, the higher the performance of human resources.Based on direct, indirect and total human resources performance model, the prioritydevelopment are as follows: Improved performance of human resources is influencedby continuance commitment are built with quality improvement of communication. Improvedperformance of human resources is influenced by normative commitment to the improvementof communication quality built. Improved performance of human resources is influenced byaffective commitment is built with improvement communication. Improved performance ofhuman resources is influenced by the quality of communication.Keywords: Performance human resources, affective commitment, continuance commitment, normative commitment, communication